Làm giúp mình bài 1 với

Question

Làm giúp mình bài 1 với
lam-giup-minh-bai-1-voi

in progress 0
Calantha 8 tháng 2020-11-02T12:20:17+00:00 1 Answers 56 views 0

Answers ( )

  1. Đáp án:

    2) \(\left[ \begin{array}{l}
    x = 9\\
    x = 4\\
    x = 0
    \end{array} \right.\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    1)P = \dfrac{{2x + 4\sqrt x  + 6 + \left( {\sqrt x  – 2} \right)\left( {\sqrt x  + 3} \right) + 3\left( {\sqrt x  – 1} \right) – 2\left( {x + 2\sqrt x  – 3} \right)}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{2x + 4\sqrt x  + 6 + x + \sqrt x  – 6 + 3\sqrt x  – 3 – 2x – 4\sqrt x  + 6}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{x + 4\sqrt x  + 3}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  + 1} \right)}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{\sqrt x  + 1}}{{\sqrt x  – 1}}\\
    2)P = \dfrac{{\sqrt x  + 1}}{{\sqrt x  – 1}} = \dfrac{{\sqrt x  – 1 + 2}}{{\sqrt x  – 1}} = 1 + \dfrac{2}{{\sqrt x  – 1}}\\
    P \in Z \Leftrightarrow \dfrac{2}{{\sqrt x  – 1}} \in Z\\
     \Leftrightarrow \sqrt x  – 1 \in U\left( 2 \right)\\
     \Leftrightarrow \left[ \begin{array}{l}
    \sqrt x  – 1 = 2\\
    \sqrt x  – 1 =  – 2\left( l \right)\\
    \sqrt x  – 1 = 1\\
    \sqrt x  – 1 =  – 1
    \end{array} \right. \to \left[ \begin{array}{l}
    \sqrt x  = 3\\
    \sqrt x  = 2\\
    \sqrt x  = 0
    \end{array} \right.\\
     \to \left[ \begin{array}{l}
    x = 9\\
    x = 4\\
    x = 0
    \end{array} \right.
    \end{array}\)

Leave an answer